The search‐based scheduling algorithm HP* for parallel tasks on heterogeneous platforms. (1st July 2020) - Dietze, Robert; Rünger, Gudula
Summary: Scheduling is a widely used method in parallel computing, which assigns tasks to compute resources of a parallel environments. In this article, we consider independent parallel tasks to be scheduled onto a heterogeneous execution platform consisting of a set of multicores of different architecture. Each parallel task has an internal potential parallelism which allows a parallel execution on any multicore processors. However, the execution time may differ due a different computation speed of different multicores. In this article, we propose a new search‐based scheduling algorithm Heterogeneous Parallel task scheduling based on A* (called HP* ) to solve the problem of scheduling independent parallel tasks onto heterogeneous multicore platforms. Specifically, we propose a heuristic cost function needed for an informed search. Also, three pruning techniques are proposed, which are shown to significantly reduce the search space of HP* . Performance measurements on a heterogeneous platform are performed and the results of HP* are compared to scheduling results of other popular scheduling methods. The performance results with benchmark tasks from the SPLASH‐3 benchmark suite demonstrate the good scheduling results and the improvements achieved by HP* .